Effect of different sources of starch and guar gum on aqua stability of shrimp feed pellets - Ali, S Ahamad; Gopal, C; Ramana, J V; Nazer, A R (Indian Journal of Fisheries, 2011)
A shrimp feed formulation, consisting of fishmeal, squid meal, prawn head meal, soybean meal, cereal flour (different sources), fish oil, lecithin and other feed additives was selected for evaluating aquastability of different sources ofstarch namely, corn flour, maida flour, rice flour, tapioca flour and wheat flour as binders at 15.3% each in combination with guar gum at three levels of 1, 2 and 3%. The feed pellets were prepared (3-5 mm length, 3mm diameter) by adding 40 ml water for 100g dry powdered feed mix followed by steaming,pelleting in hand pelletizer and drying at 70o C. The aqua-stability of feed pellets was determined by measuring the loss in weight of pellets soaked in water and the turbidity of water as Nephlometer reading (NMR). Among the starch sources tested, maida flour in combination with 2% guar gum in thefeed imparted better aqua-stability to pellets followed by tapioca flour, rice flour, wheat flour and corn flour. Further increase in the level of guar gum in feed had no beneficial effect. It was observed that pellets containing guar gumrapidly swelled and developed cracks and these effects were higher with increase in guar gum level.